Fractional flow reserve guided versus angiographic guided surgical revascularization: A meta‐analysis. Issue 1 (14th December 2020) - Bruno, Francesco; D'Ascenzo, Fabrizio; Marengo, Giorgio; Manfredi, Roberto; Saglietto, Andrea; Gallone, Guglielmo; Franchin, Luca; Piroli, Francesco; Angelini, Filippo; De Filippo, Ovidio; Conrotto, Federico; Omedè, Pierluigi; et al.
Abstract: Background: Clinical benefits of FFR (Fraction Flow Reserve) driven CABG (Coronary Artery Bypass Graft) remain to be established. Methods: All randomized controlled trials (RCTs) and observational studies with multivariable adjustement were included. MACE (Major Adverse Cardiac Events) was the primary end point, while its single components (death, myocardial infarction, and total vessel revascularization [TVR]) along with number of anastomoses, on pump procedures and graft occlusion at angiographic follow‐up were the secondary ones. Each analysis was stratified for RCTs versus observational studies. Results: Four studies (two RCTs and two observational) were included, enrolling 983 patients, 542 angio‐guided and 441 FFR‐guided. Mean age was 68.45 years, 79% male, with a mean EuroSCORE I of 2.7. Coronary lesions were located in 37% of patients in the left anterior descending artery, 32% in the circumflex artery, and 26% in the right coronary artery. After a mean follow‐up of 40 months, risk of MACE did not differ (OR 0.86 [0.63–1.18]) as that of all cause death (OR 0.86 [0.59–1.25]), MI (OR 0.57 [0.30–1.11]) and TVR (OR 1.10 [0.65–1.85]). FFR‐driven CABG reduced on‐pump procedures (OR 0.58 [0.35–0.93]) and number of anastomoses (−0.40 [−0.80: −0.01]) while incidence of graft occlusion at follow‐up did not differ (OR 0.59 [0.30–1.15], all CI 95%). Conclusion: Fraction flow reserve driven CABG reduced the number of anastomoses and of on‐pump procedures without increasing risk of MACE and without reducing graft occlusion at angiographic follow‐up. ID CRD42020211945.